Systematic review on sports performance in beach volleyball from match analysis - Araripe Medeiros, A. I.; Palao, J. M.; Marcelino, R.; Mesquita, I. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
The present article aimed to perform a systematic review of the available literature in relation to the analysis of sports performance in beach volleyball from match analysis. Web of Science, SportDiscus®, PubMed, Scopus and Academic Search Complete databases were used to identify peer-reviewed published articles. The authors conducted a content analysis according to goals, variables of analysis and methods used in studies. In general, three research lines were determined: analysis of the functional dependence of the game actions and their relation with success, performance according to gender, and the effect of changing the rules on the game performance. In relation to methodology, an evolution from descriptive studies to studies of comparative nature can be seen and, more recently, there has been a focus on predictive nature. This new trend breaks with the research based on simple cause and effect relations, and focuses on the analysis of the game events, namely related to tactical-technical performance indicators, in a non-linear and interactive way, considering the game as a complex and dynamic system. The limitations of the studies analyzed show the need for further studies to investigate the identification of game patterns for the different game levels; integration of situational variables in the study of the performance of teams (such as match status and the quality of opposition).